Crebanine induces ROS-dependent apoptosis in human hepatocellular carcinoma cells via the AKT/FoxO3a signaling pathway - Tan, Jiajie; Xiang, Yuling; Xiong, Yuanguo; Zhang, Yaoyuan; Qiao, Boyang; Zhang, Hong (Frontiers in Pharmacology, 2023)
Hepatocellular carcinoma (HCC), as an aggressive cancer with a high mortality rate, needs high-efficiency and low-toxicity drug therapy. Natural products have great potential as candidate lead compounds for the development of new HCC drugs. Crebanine is an isoquinoline alkaloid derived from Stephania with various potential pharmacological effects such as anti-cancer. However, the molecular mechanism underlying crebanine-induced liver cancer cells apoptosis has not been reported. Here, we investigated the effect of crebanine on HCC and identified a potential mechanism of action. It was shown that crebanine effectively inhibited the growth and capacity of HepG2 cells migration and invasion in a dose-dependent manner. Furthermore, the effect of crebanine on the morphology of HepG2 cells was observed through microscopy. Meanwhile, crebanine induced apoptosis by causing reactive oxygen species (ROS) burst and mitochondrial membrane potential (MMP) disrupt. We found that crebanine could down-regulate Bcl-2 and up-regulate Bax, cleaved-PARP, cleaved-caspase-3 and cleaved-caspase-9, but these effects were overturned by ROS inhibitor N-acetylcysteine (NAC).Crebanine also down-regulated p-AKT and p-FoxO3a,and the PI3K inhibitor LY294002 significantly enhances this effect. We also found that the expression of AKT/FoxO3a signaling pathway was ROS-dependent. As shown by Western blots, NAC could partially attenuate the inhibitory effect of crebanine on AKT and FoxO3a phosphorylation. Based on our results, our results suggest that crebanine,as a compound with potential anticancer activity, has significant cytotoxic effects on hepatocellular carcinoma,and it likely induces apoptosis via ROS in the mitochondrial pathway and simultaneously affects the biological function of HCC via the ROS-AKT-FoxO3a signaling axis.